Non-destructive material characterization methods - Akira Otsuki; Manasa Mohan; Sabu Thomas; Seiko Jose (Amsterdam, Netherlands Elsevier, 2023)
"Non-Destructive Material Characterization Methods provides readers with a trove of theoretical and practical insight into how to implement different non-destructive testing methods for effective material characterization. The book starts with an introduction to the field before moving right into a discussion of a wide range of techniques that can be immediately implemented. Various imaging and microscopy techniques are first covered, with step-by-step insights on characterization using a polarized microscope, an atomic force microscope, computed tomography, ultrasonography, magnetic resonance imaging, infrared tomography, and more. Each chapter includes case studies, applications, and recent developments. From there, elemental assay and mapping techniques are discussed, including Raman spectroscopy, UV spectroscopy, atomic absorption spectroscopy, neutron activation analysis, and various others. The book concludes with sections covering displacement measurement techniques, large-scale facility techniques, and methods involving multiscale analysis and advanced analysis."
Includes bibliographical references and index.
Keywords: Non-destructive testing; Materials -- Testing